Enhancing the Well-Being of Older Adults and Young Adults with Developmental Disabilities Through an Intergenerational Community Garden: Participatory Action Research - Diane L. Keen (Global Qualitative Nursing Research)
Loneliness and lack of purpose have a negative impact on well-being for young adults with developmental disabilities (DD) and older adults. Young adults with DD often lack meaningful relationships. While some aspects of well-being remain stable as a person ages, a sense of purpose may decline as life roles diminish. The purpose of this research was to discover ways enhance well-being in adults with DD and older adults through intergenerational interaction. A participatory action research approach was used with qualitative methods that included semi-structured interviews with four young adults with DD and five older adults. Participant observation and field notes were employed to enhance the rigor of the study. A community garden was the environment for intergenerational activities. Through thematic analysis of the data, five themes of well-being were constructed: engagement, positive relationships, accomplishment, meaning and purpose, and positive emotion with elements specific to adults with DD and older adults. The study revealed ways to enlist the wisdom and knowledge of older adults to enhance the well-being of young adults with DD and consequently enhance the well-being of the older adult as well. Implications of this study include employing social capital to improve well-being through synergistic relationships.